PENERAPAN MODEL PEMBELAJARAN STUDENT TEAM ACHIEVEMENT DIVISION PADA MATERI LOGIKA MATEMATIKA KELAS X SMA - Sepriyanto yarso; Ade Mirza; Silvia Sayu (Universitas Tanjungpura, 2019)
AbstractThis study aimed to determine the effectiveness of the application of the STAD type cooperative learning model on mathematical logic material in class X Pontianak Graduation High School. The method used is descriptive method. The chosen subjects were 29 students of class X Graduation High School Pontianak. The aspect used to determine the effectiveness of learning using the STAD type cooperative learning model was student learning activities, the implementation of the teacher managing learning, student responses and completeness of student learning outcomes. The data collection techniques and tools used were direct observation techniques using observation sheets of student learning activities and the implementation of teachers managing learning, indirect communication techniques using student response questionnaires and measurement techniques using student learning outcomes tests. The research data obtained that student learning activities amounted to 49.88% with fairly active criteria, the implementation of the teacher managing learning was 3.31 with good criteria,student responses amounted to 73.08% with good criteria and completeness of results student learning in classics is 48% classified as unmet criteria. The effectiveness of learning using the STAD type cooperative learning model on mathematical logic material in class X Pontianak Graduation High School was said to be ineffective. Keywords: Cooperative, Effectiveness, STAD